CHANGE OF LEARNING BEHAVIOR OF STUDENTS BIDIKMISI 2012-2014 IN FISIP UNSYIAH - Sri Widari; Effendi Hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRAKBeasiswa merupakan salah satu fasilitas yang diberikan Universitas syiah kuala kepada mahasiswa berprestasi, salah satunya adalah beasiswa Bidikmisi. Mahasiswa bidikmisi harus meningkatkan prestasi belajarnya agar dapat mempertahankan beasiswa bidikmisi yang telah ia dapatkan. Namun yang terjadi pada saat ini mahasiswa yang mendapatkan beasiswa bidikmisi tidak dapat mempertahanan IPK nya, sehingga beasiswanya di tarik. Tujuan Penelitian ini adalah untuk mengetahui perubahan perilaku belajar mahasiswa bidikmisi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Syiah Kuala. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik observasi, wawancara dan studi lapangan. Penelitian ini dilakukan di Fisip Unsyiah. Adapun yang menjadi informan pada penelitian ini adalah 7 orang mahasiswa bidikmisi dan 1 pegawai kemahasiswaan Fisip Unsyiah. Hasil penelitian ini menyatakan bahwa faktor yang mempengaruhi perubahan perilaku belajar mahasiswa bidikmisi Fisip Unsyiah adalah lingkungan. Adapun faktor yang mempengaruhi peningkatan perubahan perilaku mahasiswa bidikmisi yakni, Lingkungan sosial pendidikan, seperti guru/dosen, administrasi, dan teman-teman sekelas. Kemudian lingkungan sosial keluarga seperti, Ketegangan keluarga, sifat-sifat orangtua, serta letak rumah. Selanjutnya faktor yang mempengaruhi penurunan  perubahan perilaku mahasiswa bidikmisi Fisip Unsyiah yakni, Kondisi lingkungan masyarakat seperti tempat tinggal mahasiswa, Lingkungan alamiah Seperti kondisi udara yang sejuk, tidak panas serta faktor materi pelajaran.Kata kunci : Perilaku, Motivasi, Beasiswa BidikmisiABSTRACT Syiah Kuala University has given scholarships to students, one of them is bidikmisi scholarship. The bidikmisi student must improve his / her learning achievement in order to maintain the bidikmisi scholarship he / she has earned. But what happens at this time students who get bidikmisi scholarship can not defend its IPK, so the scholarship in the drag. The purpose of this research is to know the change of student learning behavior of Faculty of Social and Political Sciences Faculty of Syiah Kuala University. This research uses qualitative research method with observation, interview and field study. This research was conducted in Fisip Unsyiah. The informants in this research are 7 students of bidikmisi and 1 student of Fisip Unsyiah. The results of this study states that the factors that affect the change in student learning behavior Fisip Unsyiah bidikmisi is the environment. The factors that influence the change of behavior of students bidikmisi namely, social environment education, such as teachers / lecturers, administration, and classmates. Then the family's social environment such as, family tension, parenting properties, and the location of the house. Furthermore, the factors that influence the decrease in behavior change student bidikmisi Fisip Unsyiah ie, environmental conditions such as student residence, natural environment Such as the air conditions are cool, not hot and the subject matter factors.  Keywords: Behavior, Motivation, Bidikmisi Scholarship ABSTRACT  Syiah Kuala University has given scholarships to students, one of them is bidikmisi scholarship. The bidikmisi student must improve his / her learning achievement in order to maintain the bidikmisi scholarship he / she has earned. But what happens at this time students who get bidikmisi scholarship can not defend its IPK, so the scholarship in the drag. The purpose of this research is to know the change of student learning behavior of Faculty of Social and Political Sciences Faculty of Syiah Kuala University. This research uses qualitative research method with observation, interview and field study. This research was conducted in Fisip Unsyiah. The informants in this research are 7 students of bidikmisi and 1 student of Fisip Unsyiah. The results of this study states that the factors that affect the change in student learning behavior Fisip Unsyiah bidikmisi is the environment. The factors that influence the change of behavior of students bidikmisi namely, social environment education, such as teachers / lecturers, administration, and classmates. Then the family's social environment such as, family tension, parenting properties, and the location of the house. Furthermore, the factors that influence the decrease in behavior change student bidikmisi Fisip Unsyiah ie, environmental conditions such as student residence, natural environment Such as the air conditions are cool, not hot and the subject matter factors. Keywords: Behavior, Motivation, Bidikmisi Scholarship